2013
DOI: 10.1111/ped.12048
|View full text |Cite
|
Sign up to set email alerts
|

Changing pattern of antibiotic resistance of Helicobacter pylori in children during 20 years in Jinju, South Korea

Abstract: The antibiotic resistance rates of H. pylori in Jinju had a different pattern to other regions. The antibiotic resistance rates of H. pylori showed geographic variation, and local data should be provided as a guideline for treating H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…Both drugs were approved by the Food and Drug Administration (FDA) [17] and by the European Medicines Agency (EMA), so they are available both in Europe and the United States [18]. Studies related to their use in Asian and African countries are also available [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Both drugs were approved by the Food and Drug Administration (FDA) [17] and by the European Medicines Agency (EMA), so they are available both in Europe and the United States [18]. Studies related to their use in Asian and African countries are also available [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The range of clarithromycin resistance that has been reported for 10 countries varies widely, from 13.9% to 84.9% (Table 1), and is higher in 7 countries than the rate previously reported in 14 European countries (<24.0%)29). Moreover, an increasing tendency in the rate of clarithromycin resistance has been observed in Bulgaria17), South Korea22,24), Austria23), and Japan25). Presumably, this increase is due to the increased rate of prescription of clarithromycin for the treatment of respiratory tract infections in children.…”
Section: Antimicrobial Resistance Of H Pylori In Childrenmentioning
confidence: 84%
“…In some countries, antimicrobial resistance has evolved with the use of antibacterial agents3,16). Table 1 shows recent the rates of H. pylori resistance to antimicrobials that are commonly administered to children in 10 countries17,18,19,20,21,22,23,24,25,26,27). The E-test has been established as a reliable modality for measuring antibiotic resistance to all antimicrobials, except for metronidazole for which it overestimates resistance.…”
Section: Antimicrobial Resistance Of H Pylori In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Vietnamese study, clarithromycin resistance, which exceeded 50 % in young children, was a significant cause of treatment failure. The authors suggested that clarithromycin should not be used as part of H. pylori eradication therapy in children if their antibiotic susceptibility profile is unknown [7][8][9][10]. The conclusions of the authors from these aforementioned studies reflect a distinct change in the approach to management of H. pylori infection, which is targeted therapy based on resistance profiles, rather than the disease outcomes.…”
Section: Background and Significancementioning
confidence: 99%